PENGARUH FINANCIAL STABILITY, NATURE OF INDUSTRY DAN PERGANTIAN AUDITOR TERHADAP FINANCIAL STATEMENT FRAUD PADA PERUSAHAAN MANUFAKTUR YANG LISTING DI BURSA EFEK INDONESIA PERIODE 2015-2019 - Ervia Apriani; Makhdalena Makhdalena; RM. Riadi RM. Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The presentation of financial statements is used to inform the company's financial position, performance and cash flows. Sometimes companies commit fraud by manipulating financial statements to describe good conditions. The purpose of this study was to determine the influence of financial stability, nature of industry and change in auditor on financial statement fraud. This type of research is quantitative research. The population of this study are manufacturing companies listed on the Indonesia Stock Exchange period 2015-2019 of 36 companies. The data analysis method used is path analysis. The results showed that simultaneously financial stability, nature of industry and change auditor had an effect on financial statement fraud. Meanwhile, partially only financial stability has an effect on financial statement fraud. The nature of industry and change in auditor has no effect on financial statement fraud.Key Words: Financial Statement Fraud, Financial Stability, Nature Of Industry, and Change In Auditor